Superposed epoch study of ICME sub-structures near Earth and their effects on Galactic cosmic rays - Masías Meza, Jimmy Joel (2016)
Context. Interplanetary coronal mass ejections (ICMEs) are the interplanetary manifestations of solar eruptions. The overtaken solar wind forms a sheath of compressed plasma at the front of ICMEs. Magnetic clouds (MCs) are a subset of ICMEs with specific properties (e.g. the presence of a flux rope). When ICMEs pass near Earth, ground observations indicate that the flux of Galactic cosmic rays (GCRs) decreases. Aims. The main aims of this paper are to find common plasma and magnetic properties of different ICME sub-structures and which ICME properties affect the flux of GCRs near Earth. Methods. We used a superposed epoch method applied to a large set of ICMEs observed in situ by the spacecraft ACE, between 1998 and 2006. We also applied a superposed epoch analysis on GCRs time series observed with the McMurdo neutron monitors. Results. We find that slow MCs at 1 AU have on average more massive sheaths. We conclude that this is because they are more effectively slowed down by drag during their travel from the Sun. Slow MCs also have a more symmetric magnetic field and sheaths expanding similarly as their following MC, while in contrast, fast MCs have an asymmetric magnetic profile and a sheath in compression. In all types of MCs, we find that the proton density and the temperature and the magnetic fluctuations can diffuse within the front of the MC due to 3D reconnection. Finally, we derive a quantitative model that describes the decrease in cosmic rays as a function of the amount of magnetic fluctuations and field strength. Conclusions. The obtained typical profiles of sheath, MC and GCR properties corresponding to slow, middle, and fast ICMEs, can be used for forecasting or modelling these events, and to better understand the transport of energetic particles in ICMEs. They are also useful for improving future operative space weather activities.